Pengaruh Model Pembelajaran Drill Practice dan Diskoveri Terhadap Hasil Belajar Menembak (Shooting) Bola basket - Hariyanto Hariyanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of drill practice and discovery learning models on basketball shooting learning outcomes. The study used a quasi-experimental method with a research design using a nonequivalent control group design of 2x2 with a factorial design which was carried out in all majors in class XI of SMK Negeri 1 Kramatwatu. Learning outcomes data were obtained through pretest and posttest activities. The research sample was 80 students who were taken randomly by adjusting the conditions and research objectives. The results showed a significant difference between the posttest group A and group Bl. Evidenced by the value of FO is 5.225 and Sig. is 0.025 < 0.05. Thus, it shows that Ho is rejected, and H1 is accepted. This indicates that there is a significant difference in the interaction effect of drill practice and discovery learning models on students' basketball shooting learning outcomes.